A twice curvature compensated voltage reference with double frequency compensation. (November 2020) - Liu, Xifeng; Yang, Shiwei; Lu, Jianen
Abstract: This paper presents a voltage reference (VR) with low temperature coefficient (TC) and full frequency high power supply rejection ratio (PSRR), the VR is fabricated by 0.18  μ m CMOS process. The proposed VR uses different methods to compensate for the temperature curvature of the output voltage twice. Two different methods are used to compensate PSRR in high-frequency band and low-frequency band respectively by analyzing the performance of PSRR in different frequency bands. Measurement data of samples show the TC of the proposed VR reaches 1.5 ppm/° C within temperature range from −40 °C to 120 °C, PSRR reaches −77.7 dB at 100 Hz and −47.7  dB at 1 MHz. The line sensitivity (LS) is 0.05 % /V.